Exposure to tobacco and nicotine product advertising: Associations with perceived prevalence of use among college students. Issue 8 (17th November 2018) - Kreitzberg, Daniel S.; Herrera, Ana Laura; Loukas, Alexandra; Pasch, Keryn E.
ABSTRACT: Objective : The purpose of this study was to examine the relationship between exposure to tobacco marketing and perceptions of peer tobacco use among college students.Participants : Participants were 5, 767 undergraduate students from 19 colleges/universities in the State of Texas.Methods : Students completed an online survey, in the spring of 2016, that assessed past 30 day exposure to e-cigarette, cigar, smokeless tobacco, and traditional cigarette advertising across multiple marketing channels, past 30 day use of each product, and perceived prevalence of peer use. Multi-level linear regression models were run to examine the associations between exposure to tobacco advertising and perceptions of peer tobacco use controlling for age, gender, race/ethnicity, use and school. Results : Greater exposure to advertising was associated with greater perceived prevalence of peer use.Conclusions : Given the normative effects of advertising on perceived peer tobacco use, college tobacco initiatives should include descriptive norms education to counteract inaccurate perceptions.